MINAT BERWAKAF MELALUI UANG DI LINGKUNGAN PESANTREN: PENGARUH LITERASI WAKAF DAN SIKAP TERHADAP WAKAF - Didik Gelar Permana; Firman Jofani; M. Rizqon; Nurul Huda (Jurnal Ilmiah Ekonomi Islam, 2026)
Waqf is one of the Islamic philanthropic instruments with significant potential to support social development, education, and community economic empowerment. However, the realization of waqf collection in Indonesia remains far below its estimated potential. As Islamic educational institutions, pesantren (Islamic boarding schools) hold a strategic position in promoting cash-based waqf due to their strong community networks and deeply rooted philanthropic culture. This study aims to examine the influence of waqf literacy and attitudes toward waqf on the intention to participate in waqf through money within the pesantren environment, as well as to identify the waqf model preferred by the pesantren community. This research employed a quantitative approach using a survey method involving 120 respondents consisting of students, teachers, administrative staff, and employees of Pesantren Al-Ma'tuq Sukabumi. Data were analyzed using descriptive statistics, validity testing, reliability testing, and multiple linear regression analysis. The findings reveal that waqf literacy has a positive and significant effect on the intention to participate in waqf through money (β = 0.290; p < 0.05), while attitudes toward waqf also have a positive and significant effect on such intention (β = 0.437; p < 0.05). Simultaneously, both variables significantly influence the intention to participate in waqf through money, as indicated by an F-value of 64.74 and a coefficient of determination (R²) of 0.525. Furthermore, most respondents preferred a regular waqf scheme with a small contribution amount, particularly IDR 5,000 per week, and demonstrated a high willingness to participate in a routine waqf program. These findings suggest that improving waqf literacy and fostering positive attitudes toward waqf are essential factors in developing pesantren-based waqf- through-money programs.